Hydrochemical Characterization And Water Quality Evaluation For Drinking And Irrigation Purposes Of Kosi River Water At Ramnagar, Uttarakhand - Latika Negi; Nitish K Semwal; Sandeep Datt Mandoli; M C Arya; S P S Mehta (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This study used geospatial, temporal, and statistical methods to evaluate the quality of water of Kosi River in the Ramnagar area, located in the Nainital district of Uttarakhand. Ramnagar city is located where the Kosi River enters the plain region after flowing through a hilly area. The river undergoes significant changes in terms of geography, environment, and urbanization. A total of fourteen water quality parameters including pH, electrical conductivity (EC), phosphate (PO4−), biological oxygen demand (BOD), chloride (Cl−), sulfate (SO42−), nitrate (NO3−), dissolved oxygen (DO), calcium (Ca2+), magnesium (Mg2+), sodium (Na+), TDS, turbidity and total hardness (TH) were measured in samples collected from eleven different sites to evaluate seasonal fluctuation during pre-monsoon (PRM) monsoon (MON), post-monsoon (POM) of the river in 2021. The concentration of parameters at each site is compared with their permissible limits recommended by the World Health Organization (WHO) and Bureau of Indian Standards (IS 10500: 2012) to assess their suitability for human drinking. Based on the physicochemical analysis, it can be observed that the majority of the water samples taken from the river are within the recommended permissible limits for drinking purposes. Moreover, the calculated average Water Quality Index (WQI) values for PRM (44.98), MON (38.79), and POM (33.80) fall under the excellent to good categories. Statistical analyses indicate positive correlation among most of the chemical parameters. Piper diagram illustrates that all the water samples fall in Calcium-Chloride type Hydrochemical facies, Irrigation water quality of the river water was found suitable during all the three seasons according to the result of sodium adsorption ratio and sodium percentage. Therefore, based on the WQI results, it can be inferred that the water of the Kosi River in the Ramnagar region is suitable for drinking and other domestic uses without any further treatment. Therefore, to restore the vitality and water quality of the rivers, proper water resource planning program should be developed.